1986
DOI: 10.1159/000124249
|View full text |Cite
|
Sign up to set email alerts
|

Increased Number of Angiotensin II Binding Sites Determined by Autoradiography in Anterior Pituitary of Water-Deprived and Brattleboro Rats

Abstract: Pituitary angiotensin II (ANG) binding sites were characterized by autoradiography in individual male Long Evans (LE) rats, heterozygous Brattleboro (HZ) rats, and homozygous Brattleboro (DI) rats which were water satiated or water deprived. An additional group of DI rats was treated with arginine vasopressin for 1 week. The technique utilized 8-µm pituitary sections which were incubated with 125I-[Sar1]-ANG in concentrations ranging from 25 pM to 10 nM. Angiotensin binding in the anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Angiotensin receptor density was unaffected in both magnocellular and parvocellular paraventricular nucleus of Brattleboro rats. As described earlier (27), angiotensin-receptor density was higher in the anterior pituitary gland of both homozygous and heterozygous Brattleboro rats compared with the Long-Evans strain (Fig. 2, Table 1).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Angiotensin receptor density was unaffected in both magnocellular and parvocellular paraventricular nucleus of Brattleboro rats. As described earlier (27), angiotensin-receptor density was higher in the anterior pituitary gland of both homozygous and heterozygous Brattleboro rats compared with the Long-Evans strain (Fig. 2, Table 1).…”
Section: Resultssupporting
confidence: 79%
“…Although the evidence is indirect, these results do not lend support to the hypothesis that angiotensin II increases vasopressin secretion by acting directly through angiotensin receptors on vasopressin cells. Angiotensin receptors in the anterior pituitary gland seem to be sensitive to dehydration, because they are increased in chronically dehydrated Brattleboro rats but also in acutely dehydrated normal rats (27,36). It has been suggested that angiotensin II might contribute to the stimulation of ACTH secretion in the pituitary gland, either by itself of by potentiating the effects of CRH (8,37).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DEX did not initiate transcription of reporter genes regulated by the AT1B promoter [69, 70]or the AT2 promoter [70], which is consistent with the failure of DOCA or DEX treatment in this study to modulate AT2 binding in the locus ceruleus or inferior olive, which express predominantly AT2 receptors [35]or in the pituitary, which expresses few AT2 receptors [34]. Although mineralocorticoids and glucocorticoids do not modulate pituitary AngII receptor binding, other experimental conditions can do so [33, 71, 72, 73, 74, 75]. The general pattern that emerges is that adrenal steroids selectively regulate the AT1A receptor in these tissues.…”
Section: Discussionsupporting
confidence: 72%
“…Pituitaries were obtained from the same animals used in the behavioral and the brain receptor autoradiography studies. Membrane binding analysis was performed on the pituitary because it is an easily dissectable tissue with a uniformly high density of AngII receptors [31, 32, 33, 34]. The anterior pituitaries were separated from posterior and intermediate lobes.…”
Section: Methodsmentioning
confidence: 99%
“…relationship between the natural logarithm of the optical densities of each standard concentration and the natural logarithm of the radioactivity contained in that section at any exposure of Ultrofilm 3H (13). This plot of In OD vs.…”
mentioning
confidence: 99%